2008
DOI: 10.1128/aac.00462-08
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Resistance of Candida glabrata Vaginal Isolates and Development of a Quantitative Reverse Transcription-PCR-Based Azole Susceptibility Assay

Abstract: A multiplex quantitative reverse transcription-PCR assay was developed to detect azole resistance in Candida glabrata, an important opportunistic pathogen that develops resistance rapidly. Resistance was defined as a >3-fold increase in CDR1 expression by this assay, which proved to be 100% sensitive and 95% specific in comparison to the gold standard broth microdilution assay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 20 publications
2
17
0
1
Order By: Relevance
“…Specifically, PCR methods for the detection of mutations in the FKS1 gene that confer resistance to echinocandins (211) or of EGR11 mutations or overexpression of pump genes, such as CDR1, CDR2, and MDR1 (212), have recently been described. All these experimental techniques come with the promise of much more rapid identification of resistant Candida infections than the case with traditional broth microdilution methods, thus permitting timely initiation of appropriate treatment and decreasing the rates of treatment failure (213).…”
Section: Pcrmentioning
confidence: 99%
“…Specifically, PCR methods for the detection of mutations in the FKS1 gene that confer resistance to echinocandins (211) or of EGR11 mutations or overexpression of pump genes, such as CDR1, CDR2, and MDR1 (212), have recently been described. All these experimental techniques come with the promise of much more rapid identification of resistant Candida infections than the case with traditional broth microdilution methods, thus permitting timely initiation of appropriate treatment and decreasing the rates of treatment failure (213).…”
Section: Pcrmentioning
confidence: 99%
“…RNA was extracted by using hot SDS-phenol followed by ethanol precipitation as described previously (5), suspended in 50 l nuclease-free water, and treated with RQ1 DNase (Promega) as recommended by the manufacturer. RNA (diluted to 50 ng/l) was analyzed by quantitative reverse transcription (qRT)-PCR as described previously (20), using one-step qRT-PCR on the Stratagene Mx3000P QPCR system (Stratagene). Assays (25 l) in triplicate contained 125 ng RNA, 0.6 M each primer (CDR1F and CDR1R or ACT1F and ACT1R), 0.2 M FAMlabeled probe, 12.5 l Quanta one-step master mix (2ϫ) (Quanta Biosciences), 6.5 l water, and 0.5 l Quanta Escript one-step reverse transcriptase.…”
Section: Mediamentioning
confidence: 99%
“…Surveillance programs performed over the past few decades have demonstrated that although azole resistance is rare in Candida albicans isolates (<1%), it is becoming very common among isolates of non-albican species (up to 15%) [6]. The rise in VVC infections, and more specifically in non-albicans species, could be due to several factors ranging from an increase in over-the-counter antifungal use to an increase in high-risk patient populations (i.e., sexually active young females).…”
Section: Introductionmentioning
confidence: 99%